A comparative evaluation of bone marrow biopsy and bone marrow aspiration in different haematological condition with special reference to leukaemia and lymphoma - Verma, Nidhi; Gupta, Priya; Saroj, Amod Kumar; Singh, Preeti; Karuna, Veer (International Journal of Research in Medical Sciences, 2020)
Background: For diagnosis of haematological disorders there are three modalities to examine bone marrow, bone marrow aspiration cytology (BMA), bone marrow imprint (BMI) and bone marrow biopsy (BMB). BMA gives cytological picture; BMI also gives cytological picture but cells are less in number and BMB gives cytological as well as architectural picture. BMA alone may not be sufficient to reach diagnosis therefore the present study was undertaken to compare the above modalities. The study was conducted with the aim to perform cytomorphological evaluation of bone marrow in various haematological disorders with special reference to leukaemia and lymphoma and to compare bone marrow aspiration smears with bone marrow trephine biopsy. Methods: The present study was conducted in department of pathology, LLRM Medical College, Meerut inpatients attending the outpatient department and in-patient department of pediatrics and medicine of SVBP Hospital attached to LLRM Medical College, Meerut, over a period of one year i.e. from March 2018 to May 2019. A detailed clinical history, physical examination and laboratory examination of all the cases was done. Results: Out of 50 cases, maximum number of cases were of anemia 26/50 (52%) followed by leukemia 17/50 (34%), lymphoma 5/50 (10%), multiple myeloma 1/50 (2%), myelofibrosis 1/50 (2%), leishmaniasis 1/50 (2%) and idiopathic thrombocytopenic purpura 1/50(2%). BMA smears were compared with biopsy and concordance and discordance was established. The overall diagnostic accuracy of aspiration was 94%. Conclusions: Bone marrow examination is a safe, quick easy and cost-effective procedure with very less patient discomfort. BMA shows better cellular details when compared to BMI and BMB. BMB is diagnostic investigation in dry tap cases like aplastic anemia, myelofibrosis, myelodysplastic syndrome and metastatic tumors. In present study, concordance between BMA and BMB was seen in majority of the cases and diagnostic accuracy was 94% study concludes that bone marrow aspiration cytology and trephine biopsy complement each other and should be performed simultaneously for complete bone marrow work up and evaluation.